Dietary habits and dental health over the first 18 months of life - Habibian M, Roberts G, Lawson M, Stevenson R, Harris S (Blackwell Synergy, 2001)
The main objective of this study was to describe the dental health of infants and toddlers with special reference to their dietary habits and oral hygiene behaviour over the first 18 months of life.